Estrogenic Activity of Hyperforin in MCF-7 Human Breast Cancer Cells Transfected with Estrogen Receptor - Kwon, Joseph; Oh, Kyung Seo; Cho, Se-Young; Bang, Mi Ae; Kim, Hwan Seon; Vaidya, Bipin; Kim, Duwoon (Planta Medica, 2016)
Hyperforin, a major active compound of St. Johnʼs wort extract, affects estrogenic activity. In this study, the compound evoked estrogen response element-dependent luciferase activity and cell proliferation in MCF-7 cells. Hyperforin-induced cell proliferation was significantly inhibited by the estrogen receptor antagonist ICI 182,780. These results suggested that hyperforin had estrogenic and cell proliferation activities, which were stimulated via the estrogen receptor. Compared to 17β-estradiol, hyperforin showed significantly lower estrogenic activity and cell proliferation. The mechanism underlying the estrogenic activity of hyperforin was unknown, therefore, in this study, for the first time, the expression and post-translational modification of proteins were determined and compared among control, 17β-estradiol-treated, and hyperforin-treated cells using proteomic techniques. A total of 453 proteins were identified, of which 282 proteins were significantly modulated in hyperforin-treated cells compared to 17β-estradiol-treated cells. Ingenuity pathway analysis also demonstrated that hyperforin treatment induced less cell proliferation than 17β-estradiol by downregulating estrogen receptor 1. Protein network analysis showed that cell proliferation was regulated mainly by cyclin D1 and extracellular signal-regulated kinases. In conclusion, although, hyperforin exhibited lower estrogenic activity than 17β-estradiol, the compound induced lower levels of cancer cell proliferation in vitro.
Keywords: Clusiaceae; estrogenic activity; hyperforin; Hypericum perforatum; Proteomics; St. Johnʼs wort